Cover Feature: Hybrid Conversion of 5‐Hydroxymethylfurfural to 5‐Aminomethyl‐2‐furancarboxylic acid: Toward New Bio‐sourced Polymers (ChemCatChem 1/2021). Issue 1 (7th December 2020) - Lancien, Antoine; Wojcieszak, Robert; Cuvelier, Eric; Duban, Matthieu; Dhulster, Pascal; Paul, Sébastien; Dumeignil, Franck; Froidevaux, Renato; Heuson, Egon
Abstract : The Cover Feature shows that hybrid catalysis is a very promising concept that combines chemical catalysts and biocatalysts in one‐pot processes. These are particularly useful for the diversification of synthesis routes, and especially for the valorization of compounds from biomass, offering more ecological approaches. In their Full Paper, A. Lancien et al. report a transaminase coupled to a platinum nanoparticle, both supported on silica, for the efficient conversion of 5 ‐hydroxymethylfurfural into 5 ‐aminomethyl‐ 2 ‐furancarboxylic acid. By circumventing the limitations usually associated with the synthesis of furfurylamines (dangerous and polluting reagents, energy and financial costs, etc.), this new, sustainable low‐temperature route could be useful for the conversion of lignocellulose into bio‐sourced polyamides. More information can be found in the Full Paper by A. Lancien et al.